2004
DOI: 10.1046/j.1365-2141.2003.04787.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin K influences intra‐individual variability in anticoagulant response to warfarin

Abstract: SummaryThe relationship between dietary intake of vitamin K, fat, plasma vitamin K concentrations and anticoagulation response to warfarin within individuals, as well as the contribution of dietary vitamin K to differences in warfarin dose requirements between individuals were investigated in 53 patients on warfarin therapy who had stably controlled anticoagulation. Each patient completed a dietary record of all foods consumed on a daily basis for 4 weeks. Each week a blood sample was taken for measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 31 publications
4
57
0
1
Order By: Relevance
“…However, since the activation of thrombin is inextricably linked with the vitamin K cycle in the coagulation cascade, there is the possibility that the pharmacological activity of direct thrombin inhibitors could be influenced by alterations in vitamin K availability. The enhanced pharmacological activity of warfarin in vitamin K deficient rats observed in this study confirms the well-established impact of vitamin K deficiency on anticoagulation response to warfarin in man [4][5][6][8][9][10]. This study also demonstrates that overt vitamin K deficiency enhances the anticoagulant activity of the direct thrombin inhibitor, ximelagatran, in rats.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, since the activation of thrombin is inextricably linked with the vitamin K cycle in the coagulation cascade, there is the possibility that the pharmacological activity of direct thrombin inhibitors could be influenced by alterations in vitamin K availability. The enhanced pharmacological activity of warfarin in vitamin K deficient rats observed in this study confirms the well-established impact of vitamin K deficiency on anticoagulation response to warfarin in man [4][5][6][8][9][10]. This study also demonstrates that overt vitamin K deficiency enhances the anticoagulant activity of the direct thrombin inhibitor, ximelagatran, in rats.…”
Section: Discussionsupporting
confidence: 87%
“…It has been suggested that alterations in dietary vitamin K may also explain some of the intra-patient variability [4][5][6]. Vitamin K, in its hydroquinone form, is an essential co-factor for the carboxylation of the glutamic acid residues of the amino-terminals of the coagulation proteins II, VII, IX and X, leading to their activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12 Earlier we showed that in patients with stable control of anticoagulation, for every 100-g increase in vitamin K intake in the previous 4 days, INR falls by 0.2, 16 further exemplifying the relationships between dietary vitamin K and anticoagulation response.…”
Section: Discussionmentioning
confidence: 99%
“…A large and increasing number of drugs interact with warfarin leading to over-anticoagulation, under-anticoagulation, or increased bleeding [Holbrook et al 2005;Juurlink, 2007]. Differences in the dietary content of vitamin K are known to profoundly alter the pharmacodynamic effects of warfarin [Franco et al 2004;Khan et al 2004;Kurnik et al 2004;Schurgers et al 2004;Couris et al 2006;Rohde et al 2007;De Assis et al 2009]. Warfarin is extensively metabolized in the liver by the cytochrome P-450 2C9 (CYP2C9) isoenzyme.…”
Section: Warfarinmentioning
confidence: 99%